دور التحكيم التجاري الدولي في فض المنازعات المتعلقة بالاستثمار الاجنبي - شاوش ،فاطمة الزهراء; عقاب، البشير; عماري ،مسعود (جامعة الوادي University of El Oued, 2024)
إن التحكيم التجاري الدولي يعد الأداة الأكثر نجاعة بسبب دورها في حماية الاستثمار من المنازعات التي قد تنشأ عنه، خاصة الاستثمار الأجنبي نتيجة تأثيره على البعد الاقتصاد الدولي، هذا من جهة، ومن جهة اخرى كونه الوسيلة التي اختارها أطراف النزاع بخالص إرادتهم لحل نزاعهم، وما سلكهم في هذه الطريق سوى أنها طريق الأمان نحو إنجاز استثماراتهم والحفاظ على مصالحهم، فمن جهة المستثمر تحقيق الأرباح ومن جهة الدولة استمرار النشاط الاقتصادي والقضاء على الفقر والهشاشة الاجتماعية، وعليه، يعتبر التحكيم التجاري الدولي من بين أهم الضمانات التي تجلب المستثمرين الأجانب وتشجعهم على ضخ أموال كثيرة دون أي مخاوف من قوانين الدول المضيفة وفرض سيادتها وتغيير القوانين متى ما شاءت وكيف ما شاءت، فالتحكيم هو قضاء الأطراف المتنازعة. International commercial arbitration is considered the most effective tool because of its role in protecting investment from disputes that may arise from it, especially foreign investment, as a result of its impact on the international economic dimension, on the one hand, and on the other hand, because it is the means chosen by the parties to the dispute of their pure will to resolve their dispute, and What they took on this path is that it is a safe path towards completing their investments and preserving their interests. On the investor’s side is achieving profits, and on the state’s side is the continuation of economic activity and the elimination of poverty and social fragility. Accordingly, international commercial arbitration is considered among the most important guarantees that attract foreign investors and encourage them to pump a lot of money without any fears of the laws of the host countries, imposing their sovereignty, and changing the laws whenever they want and how they want. Arbitration is the judiciary of the conflicting parties.